Hypoglycaemic Properties of Malaysian Cocoa (Theobroma Cacao) Polyphenols Extract - Azli, Ruzaidi (2006)

(untitled)
The objective of the study was to investigate the hypoglycaemic properties of Malaysian cocoa (Theobroma cacao) polyphenols extract in-vivo and in-vitro. Cocoa extract (CE) (containing 190 - 286 mg total polyphenol per gram extract) was prepared from fermented and roasted (140 Â°C, 20 min) beans by extracting with 80% ethanol in the ratio of 1 to 10. For the in-vivo study, the CE was given in three dosages (1%, 2%, and 3%) to groups of normal and diabetic rats for a period of 4 weeks by force-feeding. Results showed that dosages of 1% and 3% CE significantly reduced (p < 0.05) the plasma glucose levels in the diabetic rats. BRIN-BD11 cell lines were used to evaluate the effect of CE on insulin secretions. An in-vitro study demonstrated that CE at a concentration of 0.1 mg/ml significantly increased (p < 0.05) insulin secretion compared to the control. The results of this study showed that Malaysian cocoa polyphenol extract have the potential of being a hypoglycaemic agent. Further studies are needed to elucidate the mechanism action of polyphenols present in CE, which could be utilised to lower the plasma glucose levels and stimulate insulin secretion in patients with Diabetes Mellitus Type 2.